Vaccine wastage in The Gambia: a prospective observational study - Effua Usuf; Grant Mackenzie; Lamin Ceesay; Dawda Sowe; Beate Kampmann; Anna Roca (BMC, 2018)
Abstract Background Vaccination is a cost-effective and life-saving intervention. Recently several new, but more expensive vaccines have become part of immunization programmes in low and middle income countries (LMIC). Monitoring vaccine wastage helps to improve vaccine forecasting and minimise wastage. As the costs of vaccination increases better vaccine management is essential. Many LMIC however do not consistently monitor vaccine wastage. Methods We conducted two surveys in health facilities in rural and urban Gambia; 1) a prospective six months survey in two regions to estimate vaccine wastage rates and type of wastage for each of the vaccines administered by the Expanded programme on Immunization (EPI) and 2) a nationwide cross sectional survey of health workers from randomly selected facilities to assess knowledge, attitude and practice on vaccine waste management. We used WHO recommended forms and standard questionnaires. Wastage rates were compared to EPI targets. Results Wastage rates for the lyophilised vaccines BCG, Measles and Yellow Fever ranged from 18.5-79.0%, 0-30.9% and 0-55.0% respectively, mainly through unused doses at the end of an immunization session. Wastage from the liquid vaccines multi-dose/ single dose vials were minimal, with peaks due to expiry or breakage of the vaccine diluent. We interviewed 80 health workers and observed good knowledge. Batching children for BCG was uncommon (19%) whereas most health workers (73.4%) will open a vial as needed. Conclusion National projected wastage targets were met for the multi-dose/single dose vials, but for lyophilised vaccines, the target was only met in the largest major health facility.